Pengaruh Leverage, Likuiditas, Profitabilitas dan Ukuran Perusahaan terhadap Sustainability Report Disclosure dengan ESG sebagai Variabel Moderasi - Winasari Damanik; Maylia Pramono Sari (Universitas Budi Luhur, 2026)
This study examines the effects of leverage, liquidity, profitability, and firm size on sustainability report disclosure, with ESG serving as a moderating variable. The study uses a purposely selected sample of 30 LQ45 companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024, comprising 98 observations. This study used panel data regression and EViews 12. The results indicate that leverage, profitability, and firm size do not have a significant effect on sustainability report disclosure; however, liquidity has a positive, significant effect. Furthermore, ESG does not moderate the effects of leverage, liquidity, and profitability; rather, it enhances the effect of firm size on sustainability report disclosure.